Synthesis of cyclic beta-(1,2)-glucans by Rhizobium leguminosarum biovar trifolii TA-1: factors influencing excretion. - Breedveld, M W (1992)
The synthesis of cyclic beta-(1,2)-glucans from UDP-[14C]glucose by a crude membrane preparation and whole cells of Rhizobium leguminosarum bv. trifolii TA-1 was investigated. The crude membrane system needed Mn2+, ATP, and NAD+ for optimal activity. Hardly any difference in biosynthetic activity between membrane fractions of TA-1 cells grown in the presence (200 mM) or absence of NaCl was observed. Whole TA-1 cells grown in the presence of NaCl excreted labeled, neutral cyclic beta-(1,2)-glucan during incubation with added UDP-[14C]glucose. With NaCl-free cultured TA-1 cells, no excretion was observed; however, after these cells were alternately frozen and thawed eight times, they excreted glucans. Glucan formation in vitro and glucan excretion by whole cells were strongly inhibited in the presence of 50 mg of cyclic glucan per ml (about 15 mM), indicating that biosynthesis of cyclic beta-(1,2)-glucans in strain TA-1 is controlled by end-product inhibition. These observations indicate that TA-1 cells become more permeable to cyclic glucans at high NaCl concentrations. The constant loss of glucans from cells grown in the presence of 200 mM NaCl prevented end-product inhibition and resulted in glucan accumulation of up to 1,600 mg/liter in the medium.